2017
DOI: 10.1002/ldr.2689
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 47 Years of No Tillage and Stubble Retention on Soil Aggregation and Carbon Distribution in a Vertisol

Abstract: Aggregation often provides physical protection and stabilisation of soil organic carbon (C). No tillage (NT) coupled with stubble retention (SR) and nitrogen (N) fertiliser application (90 N, 90 kg N ha−1 application) can help improve soil aggregation. However, information is lacking on the effect of long‐term NT, SR and N fertiliser (NT, SR + N) application on soil aggregation and C distribution in different aggregates in vertisols. We analysed the soil samples collected from 0‐ to 30‐cm depth from a long‐ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 101 publications
(198 reference statements)
6
47
0
Order By: Relevance
“…The results of the different aggregate size fractions in terms of DSA indicated that the 2-1 mm and 1-0.5 mm fractions were both affected in cropland (Table 4), with the DSA at 0-20 cm increasing in the order of Clm, Clw, CAO, GL, SGL, and AAO. As many authors revealed before, farm machinery could disturb the soil aggregate fractions and ultimately affect WSA [2,4,7,36], our findings also indicated that the 2-1 mm and 1-0.5 mm fractions were destroyed by ploughing; the study findings suggest that plant restoration and a change in crop cultivation patterns could improve WSA formation in cropland, particularly in the study areas. Soil aggregation can be increased with cropland conversion to no-tillage due to the rapid turnover of SOC in the soil layers [37].…”
Section: The Dsa and Wsa Distribution Of Soil Aggregate Compositions (%)supporting
confidence: 75%
“…The results of the different aggregate size fractions in terms of DSA indicated that the 2-1 mm and 1-0.5 mm fractions were both affected in cropland (Table 4), with the DSA at 0-20 cm increasing in the order of Clm, Clw, CAO, GL, SGL, and AAO. As many authors revealed before, farm machinery could disturb the soil aggregate fractions and ultimately affect WSA [2,4,7,36], our findings also indicated that the 2-1 mm and 1-0.5 mm fractions were destroyed by ploughing; the study findings suggest that plant restoration and a change in crop cultivation patterns could improve WSA formation in cropland, particularly in the study areas. Soil aggregation can be increased with cropland conversion to no-tillage due to the rapid turnover of SOC in the soil layers [37].…”
Section: The Dsa and Wsa Distribution Of Soil Aggregate Compositions (%)supporting
confidence: 75%
“…Tisdall and Oades 79 proposed that the formation and stability of micro-aggregates and macro-aggregates were interrelated processes. A wealth of research had manifested that macro-aggregates composed of organic binding agents [80][81][82][83][84] . Consequently, the protective mechanism of macro-aggregates on SOC was better than micro-aggregates 85,86 .…”
Section: Discussionmentioning
confidence: 99%
“…Soils with contrasting texture demonstrated to benefit from no‐tillage adoption both in the medium and long period. For example, Australian clay‐rich Vertisols had better soil aggregation especially when associated with stubble retention and nitrogen fertilization after 47 years of no‐tillage adoption (Somasundaram et al, ). In Danish sandy‐loam soils, Garbout et al () observed a distinct pipe‐like macropore structure in the 0–5 cm soil layer under 7‐year no‐tillage management.…”
Section: Discussionmentioning
confidence: 99%